Optimizing YouTube Video Visibility and Engagement: The Impact of Keywords on Fisheries’ Product Campaigns in the Supply Chain Sector - Emmanouil Giankos; Nikolaos T. Giannakopoulos; Damianos P. Sakas (Information)
YouTube has emerged as a powerful platform for digital content distribution, particularly in niche sectors such as fisheries and environmental sustainability. This study examines the impact of specific keywords on video visibility and engagement, focusing on fishery-related YouTube channels within the broader supply chain context. Using a statistical analysis with R software, this study isolates the influence of keywords while controlling for macro-characteristics such as video duration, title length, and description length. The findings reveal that while most structural video attributes do not significantly impact views, keyword optimization in video titles is crucial in improving discoverability. Additionally, a positive correlation between views and user engagement (likes) is confirmed, highlighting the role of interaction in content promotion. These insights provide actionable recommendations for content creators seeking to enhance their digital outreach while offering theoretical contributions to search engine optimization (SEO) and social media marketing strategies.